Pharmaceutical Care and humanization of care: lessons from the promotion of adhesion to therapeutic care of users in chronic conditions - Pollyana Borges de Araújo Prata; Marcia Regina Cunha; Érica Gomes Pereira; Lucia Yasuko Izumi Nichiata (O Mundo da Saúde)
The high consumption of drugs is increasingly making health professionals be concerned about adherence to treatment by patients. This article aims to share experiences in pharmaceutical care performed by a Basic Health Unit (BHU) in São Paulo. The BHU pharmacy, in addition to translating prescription notes and making boxes with pictograms to guide the rational use of drugs, together with the manager and the professionals who attend the meetings of the technical service, developed an assistance strategy for medication monitoring use at home for users having more difficulties with adherence to treatment. The main lessons learned are about dealing with the importance of cooperation of the pharmacist in the Family Health Strategy to promote the rational use of drugs, and that the actions taken to enhance the adhesion of drug users should be part of the general actions for promoting subjects autonomy, that is, decisions and control over their own health. The route to be followed involves promoting an emancipatory attitude in pharmaceutical care is equal to promoting practices mediating between the knowledge of health professionals and the patients, aiming at a more qualified family health care.